(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
The pens that documented the trajectory of popular resistance in Algeria through their observation and contemporaneous witnessing of events were French pens. By virtue of this contemporaneity, they became the primary source that no researcher of resistance history can do without it. However, what is notably observed about these writings is their focus on the military and political aspects, the blatant distortion of facts, and the premeditated disregard for the media and psychological warfare against all things Algerian. Hence, we see that the Algerian researcher must reconsider these psychological aspects, as they contributed profoundly to the colonial war. In this scholarly paper, I have chosen to address this type of warfare that focused on psychological influence on Algerians in their resistance, while examining the most important methods employed and their principal theorists, leading to an illustration of manifestations of this warfare. In conclusion, we arrive at a set of findings that we hope constitute a successful attempt to study this type of warfare against resistance in southern Algeria.